Impact of isoniazid preventive therapy on mortality among children less than 5 years old following exposure to tuberculosis at home in Guinea-Bissau: a prospective cohort study. Issue 3 (26th March 2013) - Gomes, Victor Francisco; Andersen, Andreas; Lemvik, Grethe; Wejse, Christian; Oliveira, Ines; Vieira, Fina J; Carlos, Luis José; Vieira, Cesaltina da Silva; Aaby, Peter; Gustafson, Per
Abstract : Objective: In a cohort of children less than 5 years old exposed to adult intrathoracic tuberculosis (TB) in 1996–1998, we found 66% increased mortality compared with community controls. In 2005, we implemented isoniazid preventive therapy (IPT) for children exposed to TB at home, and the present study evaluates the effect of this intervention on mortality. Setting: This prospective cohort study was conducted in six suburban areas included in the demographic surveillance system of the Bandim Health Project in Bissau, the capital city of Guinea-Bissau. Participants: All children less than 5 years of age and living in the same house as an adult with intrathoracic TB registered for treatment in the study area between 2005 and 2007 were evaluated for inclusion in the IPT programme. Main outcome measures (end points): The all-cause mortality rate ratio (MRR) between exposed children on IPT, exposed without IPT and unexposed community control children. Results: A total of 1396 children were identified as living in the same houses as 416 adult TB cases; of those, 691 were enrolled in the IPT programme. Compared with community controls, the IPT children had an MRR of 0.30 (95%CI 0.1 to 1.2). The MRR comparing exposed children with and without IPT was 0.21 (0.0 to 1.1). The relative mortality in IPT children compared with community controls in 2005–2008 differed significantly from the relative mortality of exposed untreated children compared with the community controls in 1996–1998 (test of interaction, p=0.01). Conclusions: In 2005–2008, exposed children on IPT had 70% lower mortality than the community control children, though not significantly. Relative to the community control children, the mortality among TB-exposed children on IPT in 2005–2008 was significantly lower than the mortality among TB-exposed children not on IPT in 1996–1998.